The effects of Chlamydia trachomatis, Mycoplasma hominis, and Ureaplasma urealyticum loads on semen quality: Detection and quantitative analysis. (August 2022) - Dehghan, Amin; Pourmand, Mohammad Reza; Salimi, Vahid; Asbagh, Firouzeh Akbari; Foroushani, Abbas Rahimi; Sadeghi, Kaveh; Quchani, Samaneh Hosseini
Abstract: Background: The loads of Chlamydia trachomatis (CT), Mycoplasma hominis (MH), and Ureaplasma urealyticum (UU) may impact infertility, as well as cause risk of transmission. The quality and quantity of semen demonstrate male reproductive health. This study aimed to investigate the semen quality affected by CT, MH, and UU loads. Materials and methods: 130 semen samples, including infertile and fertile cases, were collected and analyzed. The whole genomic DNA was extracted, and the desired genes' plasmids were constructed. The CT, MH, and UU loads were quantified by real-time PCR. The data were analyzed using SPSS version 24. Results: The average age of participants was 35.2 ± 6.8 years. CT, MH, and UU frequency were 9.2% vs. 3.1%, 15.4% vs. 3.1%, and 15.4 vs. 3.1% in infertile and fertile men, respectively. The mean loads of CT, MH, and UU in infertile men were 6.44 log10 copies/ml (range 5.31–7), 4.24 log10 copies/ml (range 3.37–4.7), and 6.94 log10 copies/ml (range 5.08–8.69) respectively, which was significantly higher than fertile men. The findings revealed a significant correlation between CT and UU loads and semen parameters, whereas the load of MH displayed significant effects just on sperm motility, morphology, and the number of leukocytes. Conclusion: The absence of clinical manifestations may not indicate the quality of semen. The pathogens' loads may significantly influence the quality and properties of male reproductive health. Highlights: Sexually transmitted diseases are one of the most serious causes of infertility. The frequency and loads of CT, MH and UU in infertile men versus fertile men are significantly different. The presence and/or absence of CT, MH, and UU in semen may not significantly impact the quality and characteristics of semen. There is a significant positive association between the number of leukocytes and loads of CT, MH, and UU.